In the Crosshairs: Investigating Lytic Granules by High-Resolution Microscopy and Electrophysiology - Pattu, Varsha; Halimani, Mahantappa; Ming, Min; Schirra, Claudia; Hahn, Ulrike; Bzeih, Hawraa; Chang, Hsin-Fang; Weins, Lisa; Krause, Elmar; Rettig, Jens (Frontiers in Immunology, 2013)
Cytotoxic T lymphocytes (CTLs) form an integral part of the adaptive immune system. Their main function is to eliminate bacteria- and virus-infected target cells by releasing perforin and granzymes (the lethal hit) contained within lytic granules, at the CTL-target cell interface (the immunological synapse; IS). The formation of the IS as well as the final events at the IS leading to target-cell death are both highly complex and dynamic processes. In this review we highlight and discuss three high-resolution techniques that have proven invaluable in the effort to decipher key features of the mechanism of CTL effector function and in particular lytic granule maturation and fusion. Correlative light and electron microscopy allows the correlation between organelle morphology and localization of particular proteins, while total internal reflection fluorescence microscopy (TIRFM) enables the study of lytic granule dynamics at the IS in real time. The combination of TIRFM with patch-clamp membrane capacitance measurements finally provides a tool to quantify the size of fusing lytic granules at the IS.